Everyday life in a North Caucasian city during the NEP (new economic policy) period - Bulygina, Tamara Alexandrovna (Acta Scientiarum Socialium, 2012)
The main problem of this article is studied by the author within approaches „new local history”. Changes in attitudes, value priorities, ways of survival of the „former” people under the new regime is shown by the example of individual destinies of town inhabitants. The research is based on a wide range of sources and reflects both regional specificity and national trends. T. Bulygina demonstrates how new rules and concepts, new relations of the local community with the authorities invaded to everyday life of the citizens.
Keywords: Soviet system; Cossack; revkom